Analysis the Effect of Using Synchronous Motor as a Synchronous Condenser for Power Factor Improvement of 3-Phase Cage Rotor Induction Motor - Mutiar; Subianto; Daeny Septi Yansuri; Marliyus Sunarhati; Surya Dharma; Sutan Marsus (Jurnal Multidisiplin Madani, 2022)
Synchronous motors working at a capacitive power factor of 0.8 are obtained by providing a 0ver excitation, meaning operation at a capacitive power factor to improve the power factor of the system when connected to an inductive load, as is the case with an induction motor. A synchronous motor that is over-excitation will act like a capacitor and suck up the current that lead the voltage. A synchronous motor that works without a load that is given over excitation will function as a synchronous compensator whose capacitive value can be adjusted. The condition of this synchronous compensator is installed on a cage rotor induction motor as a power factor improvement. The results of this study showed that the power factor value of the induction motor before installing the synchronous compensator was cos φ = 0.88 and the reactive power was 132,84 VAR, after installing the synchronous compen sator, cos φ = 0.91 to 0.99 and the reactive power was 68 VAR to 28,2 VARs